Analisis Pengendalian Intern Pengeluaran Kas Pada PT. Aplikanusa Lintasarta Medan - Fitri Amalia; Arnida Wahyuni Lubis (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to find out how the cash disbursement internal control system is implemented and to determine the suitability of implementing the cash disbursement internal control system at PT. Applicationnusa Lintasarta with elements of internal control in achieving the objectives of the internal control system. This research uses a descriptive approach. The object studied is the cash disbursement internal control system implemented at PT. Nusa Lintasarta Application. The informants in this research were the Director and Cashier. Data collection techniques include observation, interviews, documentation and literature study. The results of this research show that the results of the list obtained through interviews with the three respondents are 75%, which means the internal control system for cash disbursements implemented at PT. Applicationnusa Lintasarta Medan is quite in accordance with the elements of internal control in achieving the objectives of the internal control system, namely organizational structure, authorization system and recording procedures, healthy practices and employees whose quality is in accordance with their responsibilities.